RANCANG BANGUN JARINGAN INTERNET MENGGUNAKAN ROUTER MIKROTIK RB2011iL-RM DENGAN WEB FILTERING UNTUK PENGGUNAAN INTERNET SEHAT DI SMK MA’ARIF NU 1 PAGUYANGAN - Joko Purnomo; Wika Purbasari; Sunaryono Sunaryono (LPPM STMIK Widya Utama, 2021)
Abstract─ Computer networks are very much needed in an era of increasingly fast and advanced technology. More and more users are increasing every year, especially in the field of education which has an online learning system and departments related to computers and information technology. That's why researchers took research at SMK Ma'arif Paguyangan to get to a healthy internet by utilizing web filtering, so that Students and female students can be filtered when visiting the web. For the research conducted at SMK Ma'arif nu 1 Paguyangan, in this study the method used to build a computer network using the Network Development Lifecycle (NDLC) model. Keywords─, RB2011iL-RM, web filtering.